Implications of Municipal Revenue Collection on Service Delivery in South Africa: Challenges and Recommendations - Khensani Richard Chauke; Chanthal Ronald; Makofe Mokhachane Lepheana; John Mamokhere (Journal of Governance Risk Management Compliance and Sustainability, 2024)
In South Africa, citizens have protested against inadequate services provided by municipalities across different provinces. It is argued that most protests were caused by poor service delivery, a lack of community engagement, corruption, mismanagement of public resources, lack of institutional capacity and unqualified personnel. Thus, this study evaluates the difficulties associated with revenue collection and its implications on service delivery. To assess this aim, the study adopted a qualitative research approach. This study reviewed secondary data from different databases. The study keywords were used to search for relevant studies. The study was analyzed using a thematic content approach. Moreover, the study adopted two theoretical frameworks namely; ability to pay and the benefits theory. The key findings of this study include substantial difficulties in revenue collection, which in turn affect the provision of services. Poor service delivery is continuously caused by a lack of sufficient financial resources and ineffective revenue collection mechanisms. This study indicates a significant link between low revenue collection and inadequate service delivery. The recommendations of this study to municipalities include employing qualified officials, creating rebates and discounts for paying consumers, regularly examining critical credit regulations, guaranteeing high-quality service, and boosting revenue collection in light of these findings.